Critical Thinking: A Prerequisite for a New Economics Paradigm - mouatt, simon (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
In this paper I posit that most of the serious existential crises faced by humanity are, directly or indirectly, derived from a flawed, yet surprisingly resilient, economic philosophy. The free-market system has certainly produced some benefits, which may counterbalance some of its detrimental impact, but given the persistence of euphemistic and managed narratives in the mainstream political, academic, and media realms, most critical debate is stifled. The paper suggests that it is imperative for the extant research paradigm to be first fully critiqued, then transformed, and finally adopted by the political classes. If a new paradigm gains sufficient traction, however, it will have succeeded where the neoliberal critics of the last fifty years have failed. This paper hopes to offer people fresh insight into this hitherto insurmountable problem.